Handbook of correctional mental health - Scott, Charles L. (American Psychiatric Publ., 2010)
Overview of the criminal justice system / Charles L. Scott -- Criminal justice system and offenders placed in an outpatient setting / Erik Roskes ... [et al.] -- Legal issues regarding the provision of care in a correctional setting / Charles L. Scott -- The mental health professional in a correctional culture / Kenneth L. Appelbaum -- Conducting mental health assessments in correctional settings / Humberto Temporini -- Continuous quality improvement and documentation / Amanda Ruiz -- Evaluating and treating substance use disorders / Tracy D. Gunter -- Managing disruptive and aggressive inmates / Steven J. Helfand -- Suicide prevention in correctional facilities / Lindsay M. Hayes -- Assessment of malingering in correctional settings / Michael J. Vitacco, Richard Rogers -- Trauma and incarcerated persons / Nancy Wolff, Jing Shi -- Psychopharmacology / Kathryn A. Burns -- Creating wellness through collaborative mental health interventions / Shama B. Chaiken, Catherine Prudhomme --